Aktivitas Antioksidan dan Organoleptik Minuman Probiotik Kombucha Bunga Telang (Clitoria ternatea L) Terhadap Variasi Konsentrasi Madu - Raisa Fadilla (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
This study aimed to evaluate the effect of varying honey concentrations on the antioxidant activity, chemical properties, and organoleptic quality of a probiotic kombucha beverage prepared from Clitoria ternatea L. The research was motivated by increasing exposure to free radicals due to environmental pollution and the demand for alternative natural antioxidants. Kombucha was produced with honey concentrations of 10%, 20%, and 30% (w/v), and analyses were performed using the DPPH assay for antioxidant activity, measurements of pH, total acidity, and total phenolic content for chemical properties, as well as sensory evaluations by trained panelists. The results showed that kombucha with 10% honey exhibited the lowest IC₅₀ value, indicating the highest antioxidant activity, while higher concentrations increased the total phenolic content without significantly enhancing the effective antioxidant potential. These findings suggest that excessive honey addition does not necessarily improve the functional benefits of the product, indicating the need for further formulation optimization to develop a high-quality, marketable probiotic beverage.